Activities in favour of sustainable development undertaken by Wilanow Palace Museum - Latawiec, Michał (Studia Ecologiae et Bioethicae, 2008)
The article presents Wilanow Palace Museum as a centre of culture in the context of sustainable development. After giving an outline of definition related to sustainable development and presenting the statute of this institution, the article introduces fields of Museum’s activities that are connected with the idea of sustainable development, these activities included conducting educational mission, supporting authorities of the Wilanow in maintaining sustainable development of Wilanow district and efforts undertaking by Wilanow Palace Museum on its own initiative.